Baryonic impact on the dark matter distribution in Milky Way-sized galaxies and their satellites - Zhu, Qirong; Springel, Volker (Monthly notices of the Royal Astronomical Society, 2016)
We study the impact of baryons on the distribution of dark matter in a Milky Way-sized halo by comparing a high-resolution, moving mesh cosmological simulation with its dark matter-only counterpart. We identify three main processes related to baryons - adiabatic contraction, tidal disruption, and reionization - which jointly shape the dark matter distribution in both the main halo and its subhaloes. The relative effect of each baryonic process depends strongly on the subhalo mass. For massive subhaloes with maximum circular velocity vmax > 35 km s−1, adiabatic contraction increases the dark matter concentration, making these haloes less susceptible to tidal disruption. For low-mass subhaloes with vmax < 20 km s−1, reionization effectively reduces their mass on average by ≈30 per cent and vmax by ≈20 per cent. For intermediate subhaloes with 20 km s−1 < vmax < 35 km s−1, which share a similar mass range as the classical dwarf spheroidals, strong tidal truncation induced by the main galaxy reduces their vmax. As a combined result of reionization and increased tidal disruption, the total number of low-mass subhaloes in the hydrodynamic simulation is nearly halved compared to that of the N-body simulation. We do not find dark matter cores in dwarf galaxies, unlike previous studies that employed bursty feedback-driven outflows. The substantial impact of baryons on the abundance and internal structure of subhaloes suggests that galaxy formation and evolution models based on N-body simulations should include these physical processes as major components.